Penguatan Literasi Al-Qur'an Peserta Didik Sebagai Peningkatan Minat Baca Al-Qur'an Peserta Didik di SD Negeri 69 Batu Tiroa Kabupaten Bantaeng - Wahyu Muh. Syata; Nur Fahmi Indriani; Bellona Mardhatillah Sabillah (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Al-Qur'an literacy is a mastery skill in developing three main abilities in interacting with the Al-Qur'an, these abilities are the ability to read, write and memorize the Al-Qur'an. To foster a sense of love for the Qur'an from an early age, a program to strengthen Al-Qur'an literacy was held at SD Negeri 69 Batu Tiroa. The purpose of this study is to describe how the implementation of strengthening Al-Qur'an literacy as an increase in students' interest in reading the Al-Qur'an at SD Negeri 69 Batu Tiroa. This study uses qualitative research. Data collection techniques from this study are in the form of observation, interviews, and documentation. The implementation of Al-Qur'an literacy at SD Negeri 69 Batu Tiroa is still very minimal or still in the early stages, namely still in the process of learning iqra volumes 2 to 3 and there are even some students who are still in the stage of just starting to read Al-Qur'an The Qur'an or in other words is still in the process of learning iqra volume 1. The obstacles faced during the implementation of Al-Qur'an literacy at SD Neger 69 Batu Tiroa are students who are still unable to read the Qur'an and do not have full awareness to carry out Al-Qur'an literacy which is carried out. Therefore, it is hoped that there will be attention from teachers and parents so that students are able to read, write, and memorize the Al-Qur'an properly